Animalia, Homo, and the Kingdom of God - Tuttle, Russell H. (Zygon, 2006)
Abstract. I selectively and critically review the state of knowledge about human evolution and the place of humans vis-à-vis living apes, with emphasis on bipedal posture and locomotion, expansion of the brain and associated cognitive capacities, speech, tool behavior, culture, and society. I end with a personal perspective on God and Heaven.